Strategic agility Dimensions and adapted In business organizations/ Field research analytical in Asiacell Mobile Telecommunications - عبد الرحيم, سناء; فاضل, علا (Journal of Economics and Administrative Sciences, 2016)
ract         This reaserch seeks To answer Wondering :(Is there a possibility employ strategic agility In companies sample Serving in Iraq ?)       This reaserch aims: explore Strategic Agility rely upon Dimensions that interact with each other to form the intcllectual frame Strategic Agility, These dimensions are: (Clarity of vision, Selected Strategic  Targets , Core capacities, Shared responsibility, Taking action, Empowerment, Organic Structure, Planning Strategy, Organizational learning, Information technology,  Human resourse management , Organized) .      ( Design / methodology / approach) : The study was based on the case study method for mobile communications sector in my company) Zain and Asiacell (and has been used questionnaire to collect data, hypotheses were tested through the use of some statistical treatments.           Findings : The research found that Asiacell did not qualify because the so-called (agile organization) manner characteristic of efficiency or response or speed or flexibility, and so characteristic of agile organizations, as well as interesting Asiacell nature of the vision and mission of the company in terms of its knowledge of its objective of presence as a private, and this applies in terms of take caution and confidentiality of communications, including providing the privacy of the individual user, which enhances the vision in this regard is the presence of the regulator sober her and each contact companies, namely, (the media and communications).        The practical implications: puts Find useful measure of agility strategy to help managers and decision makers to use to assess the current situation by the dimensions of agility strategy, and undoubtedly it will help to provide knowledge and understanding of the employees of those companies about the importance of these dimensions.          Originality / value: frame of this research range of knowledge through the dimensions of strategic agility, which is the modern era for the Arab term studies, as well as the research works to strengthen the strategic agility in the Iraqi companies and organizations.